Board Quality and Risk Disclosure: Evidence from Saudi Arabian Publicly Listed Companies - Alsheikh, Awatif; Alsheikh, Warda (International Journal of Supply Chain Management, 2020)
Abstract This paper investigates the effect of the board quality on risk reporting in specific social and cultural context of Saudi Arabia for a sample of 423 company-year observations over the period 2015-2018. The paper utilizes a comprehensive risk reporting index and self-constructed index of board quality to measure the main variables. Using pooled OLS regression models, our results suggest that there is a positive and significant relationship between the quality of the board of directors and risk reporting in Saudi non-financial firms. In addition, this finding is consistent with the disaggregation of the risk disclosure index into mandatory versus voluntary risk disclosures and the disclosure of financial and non-financial risk disclosures. Such findings suggest that the quality of the board of directors helps to eliminate information asymmetry and agency costs. Finally, the findings of this study can prove to be of great value to market regulators in their attempts to improve the corporate governance in Saudi Arabia and can be extended to include other countries in the MENA region.